Irradiation Effects on Structural Alloys for Nuclear Reactor Applications 1970
DOI: 10.1520/stp26641s
|View full text |Cite
|
Sign up to set email alerts
|

Axial Fatigue of Irradiated Stainless Steels Tested at Elevated Temperatures

Abstract: Uniaxial fatigue properties from tests at 400, 500, 600, and 700 C on Type 304, 304L (Ti modified), and 316 stainless steel specimens irradiated at 450 C in sodium and 750 C in argon at fluences of 0.03 to 9.3×1021 n/cm2, E>0.1 MeV, are given and compared with control specimens. Material was tested in the annealed, cold-worked, and chilled-swaged-tempered condition, while primary controls received a pretest anneal of 1500 h at 750 C. The data at 400, 500, and 600 C are compared with proposed design curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, the effect of irradiation is not generally considered in fatigue analyses of reactor structures. Some studies have carried out fatigue tests under different irradiation test conditions but obtained different (even contradictory) test conclusions [ 16 , 17 , 18 , 19 ]. Under certain irradiation test conditions, the fatigue life of the sample without irradiation is 1.5–2.5 times that of the sample with irradiation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of irradiation is not generally considered in fatigue analyses of reactor structures. Some studies have carried out fatigue tests under different irradiation test conditions but obtained different (even contradictory) test conclusions [ 16 , 17 , 18 , 19 ]. Under certain irradiation test conditions, the fatigue life of the sample without irradiation is 1.5–2.5 times that of the sample with irradiation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have carried out fatigue tests under different irradiation test conditions but obtained different (even contradictory) test conclusions [ 16 , 17 , 18 , 19 ]. Under certain irradiation test conditions, the fatigue life of the sample without irradiation is 1.5–2.5 times that of the sample with irradiation [ 16 , 17 ]. However, Zhong [ 18 ] found that the fatigue life of an irradiated sample was three times greater than that of a non-irradiated sample.…”
Section: Introductionmentioning
confidence: 99%